Disorderly women and the order of God: an Australian feminist reading of the Gospel of Mark - Connolly, Michele A. (Bloomsbury T&T Clark, 2018)
Acknowledgments -- Introduction -- 1. The Postcolonial Religious World in Australia -- 2. Colonial Australia as the Imperialised Reading Context -- 3. The Myth of Colonial Australia in an Imperial War -- 4. The Gospel of Mark, a Christian Narrative of the First Century C.E. -- 5. Jesus and Women in Mark 1-12 -- 6. Jesus in the Midst of Women, Mark 14-16 -- 7. Conclusion -- Appendices -- Indexes